Analisis Product Quality Terhadap Customer Satisfaction Melalui Customer Value Sebagai Variabel Intervening (Studi Kasus Pada PT KLW) - Gunawan, Novita Cicilia; Herdinata, Christian (Universitas Islam Kadiri, 2023)
PT KLW (company name disguised) is a cigarette manufacturer established in Surabaya and registered as a public company. Based on fluctuating data from PT KLW's sales compared to similar companies, pre-survey results in the form of PT KLW's consumer criticism and suggestions, and comparisons of PT KLW with similar companies, as well as differences in the results of previous studies, so this research is important to do, namely regarding the effect of Product quality on Customer satisfaction through Customer Value as an Intervening Variable in a Case Study in the Tobacco Products Industry. The population in this study were consumers from PT KLW in Surabaya, especially Tegalsari district. The sample used in this research is consumers of PT KLW products. The analytical method used is Partial Least Square Structural Equation Modeling (SEM-PLS). The results of the study show that Product quality variables have a significant effect on Customer Value variables, Product quality variables have a significant effect on Customer satisfaction variables, Customer Value variables have a significant effect on Customer satisfaction, and Product quality variables have a significant effect on Customer satisfaction through intervening Customer Value variables. This shows that increasing Product quality has an impact on Customer Value obtained by consumers and in the end the expected Customer satisfaction is achieved.